A stratospheric mission – design of a conceptual framework to bring weather balloons and STEM into the classroom - Connolly, Cornelia; Johnson, Patrick; Johnson, Kevin; Fitzpatrick, Mary; O’Keeffe, Derek T. (Frontiers in Education, 2023)
Introduction Integrated STEM education makes learning relevant and applicable, blending the mindset, skillset, and toolset necessary in developing a depth of understanding for science, technology, engineering and mathematics. Methods Based on the theoretical framework of Kelley and Knowles the ‘Spaceship Earth’ project was designed to engage primary school children in 4th class (ages 9 and 10 years old) in real-world project-based experiments in the classroom that are used to develop collaborative problem-solving skills and a framework for asking and answering scientific questions. This project involved researchers from two Universities and the Irish National Meteorological Service working collaboratively on a high-altitude balloon mission. Results High-altitude balloons have an established track record of safe and effective use in weather forecasting, astronomy, and STEM outreach. During the project lifecycle the children devised experiments that they launched to the stratosphere using the high-altitude balloons. Once the experiments returned to Earth, the children engaged in analysis and discussion about their experiments that extended and deepened their learning. Discussion This celestial project framework represents a new dawn of innovation for STEM education and public engagement.